Age determination of metal-poor halo stars using nucleochronometry - Christlieb, Norbert (Astronomische Nachrichten, 2016)
I describe the method of nucleochronometry for determining individual ages of stars, and report on results of the application of this method to old, metal-poor stars belonging to the Galactic halo population. I discuss uncertainties and caveats of this age determination method.